Islamic Educational Philosophy as a Foundation for Character Education in Schools - Reno Aji Prayitno; Ali Patoni; Mufid Renov Maradika; Siti Mahmudah Noorhayati (PT. Education Research Center, 2026)
Character education has become a central concern in contemporary education due to increasing moral, social, and technological challenges among learners. Various problems such as declining discipline, dishonesty, weak responsibility, low social concern, and identity crises indicate that education should not only emphasize cognitive achievement but also strengthen moral and spiritual formation. This study aims to analyze Islamic educational philosophy as a foundation for character education in schools through ontological, epistemological, and axiological perspectives. This research employs a qualitative approach using library research. Data were obtained from books, scholarly journal articles, legal documents, and relevant academic sources related to Islamic educational philosophy and character education. The data were analyzed through content analysis and philosophical interpretation. The findings show that Islamic educational philosophy provides a comprehensive framework for character education through the concepts of tawhid, fitrah, akhlaq, and insan kamil. Ontologically, learners are viewed as human beings endowed with moral potential. Epistemologically, Islamic education integrates revelation, reason, and experience. Axiologically, noble character is positioned as the ultimate goal of education. This study contributes to the development of Islamic values-based character education that is holistic, integrative, and relevant to the digital era.